2019
DOI: 10.2478/acs-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

Use of zeolites for macronutrients removal from wastewater

Abstract: Natural or synthetic zeolites have unique physical, chemical and structural properties that predetermine their use in many processes, including wastewater treatment. This study presents the results of our preliminary research in the field of nitrogen and phosphorus removal using adsorption and adsorptive ozonation with natural and modified zeolites. Iron-modified zeolite was the most efficient for the removal of ammonium nitrogen by adsorption. Phosphorus removal efficiency using adsorption was relatively low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The phenomenon is probably due to the fact that the column depth was not sufficient enough to remove the majority of the dissolved solids, including phosphorus. In the literature, some other studies, such as the one conducted by Urminská et al [47], observed that natural zeolite faces a significant challenge in the removal of phosphorus.…”
Section: Removal Efficienciesmentioning
confidence: 99%
“…The phenomenon is probably due to the fact that the column depth was not sufficient enough to remove the majority of the dissolved solids, including phosphorus. In the literature, some other studies, such as the one conducted by Urminská et al [47], observed that natural zeolite faces a significant challenge in the removal of phosphorus.…”
Section: Removal Efficienciesmentioning
confidence: 99%